POTENTIAL OF PUMPKIN SEEDS UNDER DIFFERENT SOAKING PERIODS - Sales, M. A. L.; Moreira, F. J. C.; Ribeiro, A. A.; Monteiro, R. N. F.; Sales, F. A. L (Revista Brasileira de Engenharia de Biossistemas, 2015)
This study aimed to evaluate seed germination submitted to immersion in water for different periods and early growth of squash pumpkin seedlings ’exposure’. The study was conducted in a greenhouse on the premises of IFCE, Sobral Campus. The experimental design was a complete randomized block design with four replications of 16 seeds each. Pumpkin seed squash ’exposure’ undergone treatment in the pre-soak sowing four periods (0, 24, 48, 72 hours). The variables analyzed were: first count; germination speed index; germination; mean germination time; plant height; stem diameter; number of sheets; leaf area; Air dry weight and root dry weight. Significant difference was observed only for the first count variable, leaf area, number of leaves. The percentage of seed germination in the control treatment was 11% higher compared to the germination of treatment 48 hours of soaking. It is recommended not to soak the seeds or are immersed for 24 hours because these two treatments was obtained better results.